2018
DOI: 10.1155/2018/4246703
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Biomarkers and Molecular Mechanism Investigation for Glioblastoma Multiforme Utilizing WGCNA

Abstract: To reveal the potential molecular mechanism of glioblastoma multiforme (GBM) and provide the candidate biomarkers for GBM gene therapy. Microarray dataset GSE50161 was obtained from GEO database. The differentially expressed genes (DEGs) were identified between GBM samples and control samples, followed by the module partition analysis based on WGCNA. Then, the pathway and functional enrichment analyses of DEGs were performed. The hub genes were further investigated, followed by the survival analysis and data v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 43 publications
(42 reference statements)
2
75
0
Order By: Relevance
“…Only 205 genes were unclassified in any module (in grey), accounting for 10.50% of DEGs. In comparison, previous studies have reported an average gene number in each module of 216 to 336 and percentage of genes not found in any module of 5.67%-33.61% of DEGs (Liu X et al, 2017;Liu Z et al, 2018;Yang Q et al, 2018;Zuo Z et al, 2018). In conclusion, our WGCNA results were comparable.…”
Section: Discussionsupporting
confidence: 63%
“…Only 205 genes were unclassified in any module (in grey), accounting for 10.50% of DEGs. In comparison, previous studies have reported an average gene number in each module of 216 to 336 and percentage of genes not found in any module of 5.67%-33.61% of DEGs (Liu X et al, 2017;Liu Z et al, 2018;Yang Q et al, 2018;Zuo Z et al, 2018). In conclusion, our WGCNA results were comparable.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, WGCNA has been widely applied to screening candidate susceptible genes or therapeutic targets at transcriptional level in previous studies . Abundant tumor‐associated microarray data sets were analyzed by this well‐designed method; thus, several hub genes associated to clinical traits have been investigated in various types of cancers such as breast cancer, osteosarcoma, and glioblastoma multiforme …”
Section: Introductionmentioning
confidence: 99%
“…11 Abundant tumor-associated microarray data sets were analyzed by this well-designed method; thus, several hub genes associated to clinical traits have been investigated in various types of cancers such as breast cancer, osteosarcoma, and glioblastoma multiforme. [11][12][13] In this study, we constructed a gene co-expression network and identified 15 modules using R package WGCNA based on the data from GSE31056. Key modules associated with tumor site, risk of recurrence, outcome, and survival time of TSCC were identified, and the function enrichment analysis of genes in the pink modules was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Further, thresholding power β based on the criterion of approximate scale-free topology was selected for constructing a weighted gene network. The soft threshold calculates adjacency ranging from 0 to 1, so that the constructed network conforms to the power-law distribution and re ects the real biological network state [28]. In addition, the scale-free gene network was constructed and genes with similar patterns of expression (modules) were identi ed using blockwiseModules function in the WGCNA package.…”
Section: Wgcna Analysismentioning
confidence: 99%
“…Moreover, the area under curve (AUC) was calculated usingpROCR package [33]. Larger AUC value of a gene indicated that it can effectively distinguish stroke from the control samples, and the hub gene with AUC > 0.6 in the three datasets was de ned as a diagnostic e ciency gene [28,34].…”
Section: Hub Gene Identi Cation and Validationmentioning
confidence: 99%